eXtended Reality (XR) experiences in museums for cultural heritage: a systematic review - Silva, Manuel (2023)
The incorporation of different types of media promotes a multimodal approach to the dissemination, communication and exploitation of Cultural Heritage in Museums. By utilizing digital technologies allows new forms of interactions with cultural content. Cultural spaces such as museums have been integrating new digital tools, presenting their audiences immersive, interactive, and multisensory experience that is not possible in traditional exhibitions. Withing these approaches a new term of Extended Reality (XR) is emerging and increasing its role in these cultural spaces. XR is the umbrella that englobes all forms of immersion and interaction such as Augmented Reality (AR), Mixed Reality (MR) and Virtual Reality (VR). This article aims to provide a comprehensive state of the art of XR experiences for Cultural Heritage in Museums. To support this goal, a systematic review of the peer-reviewed articles was gathered from the Scopus and Web of Science databases. Results are analyzed and the case studies are presented in this paper.